OPTIMASI JARINGAN SYARAF TIRUAN MENGGUNAKAN ARTIFICIAL BEE COLONY PADA KLASIFIKASI PENGENALAN HURUF - Alit Indrawan, I Gusti Ngurah; Widiartha, I Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Artificial Neural Networks or commonly abbreviated as ANN is one branch of science from the field of artificial intelligence which is often used to solve various problems in fields that involve grouping and pattern recognition. This research aims to classify Letter Recognition datasets using Artificial Neural Networks which are weighted optimally using the Artificial Bee Colony algorithm. The best classification accuracy results from this study were 92.85% using a combination of 4 hidden layers with each hidden layer containing 10 neurons.